Dyadic reports of weight control practices, sedentary behaviors, and family functioning and communication between adult weight management patients and their children - Pratt Keeley J.; VanFossen Catherine A.; Kiser Haley M.; Whiting Riley; Spees Colleen; Taylor Chris A.; Eneli Ihuoma; Noria Sabrena (Wiley, 2021)
Abstract Background Parents are increasingly pursuing weight loss in medical weight management programs, yet little is known about the presenting behaviors and practices of children who have parents initiating these programs. Objective To describe congruence in weight control practices, sedentary and screen time behaviors, and family functioning and communication between parents initiating a medical weight management program and their children (ages 7-18). Methods Twenty‐three dyads were enrolled and had measured height/weight and research packets completed including perceived weight status, weight control practices, sedentary and screen‐time behaviors, and family functioning and communication. Paired t‐tests and intraclass correlations assessed congruence; independent t‐tests determined differences based on child demographics (age, sex, and weight status). Results Parents underestimated children's use of weight control practices compared to child reports. Children with overweight, males, and older in age had increased weight control practices and sedentary and screen‐time behaviors. Children who perceived themselves to have overweight reported more impaired family communication than children perceived to be a healthy weight. Conclusions This study highlights the discrepancy between dyads' reports of children's behaviors, and identifies that specific child populations with overweight, older in age, and males are at‐risk of experiencing less healthy behaviors and impaired family communication. Future research should monitor changes over time in parental weight management programs to determine effects based on parental weight loss.